Updating the Definition of Cancer - Brown, Joel S.; Amend, Sarah R.; Austin, Robert H.; Gatenby, Robert A.; Hammarlund, Emma U.; Pienta, Kenneth J. (Molecular cancer research, 2023)
Most definitions of cancer broadly conform to the current NCI definition: “Cancer is a disease in which some of the body's cells grow uncontrollably and spread to other parts of the body.” These definitions tend to describe what cancer “looks like” or “does” but do not describe what cancer “is” or “has become.” While reflecting past insights, current definitions have not kept pace with the understanding that the cancer cell is itself transformed and evolving. We propose a revised definition of cancer: Cancer is a disease of uncontrolled proliferation by transformed cells subject to evolution by natural selection. We believe this definition captures the essence of the majority of previous and current definitions. To the simplest definition of cancer as a disease of uncontrolled proliferation of cells, our definition adds in the adjective “transformed” to capture the many tumorigenic processes that cancer cells adopt to metastasize. To the concept of uncontrolled proliferation of transformed cells, our proposed definition then adds “subject to evolution by natural selection.” The subject to evolution by natural selection modernizes the definition to include the genetic and epigenetic changes that accumulate within a population of cancer cells that lead to the lethal phenotype. Cancer is a disease of uncontrolled proliferation by transformed cells subject to evolution by natural selection.